Development and evaluation of an ultrasonic personal aerosol sampler. (20th July 2016) - Volckens, J.; Quinn, C.; Leith, D.; Mehaffy, J.; Henry, C. S.; Miller‐Lionberg, D.
Abstract: Assessing personal exposure to air pollution has long proven challenging due to technological limitations posed by the samplers themselves. Historically, wearable aerosol monitors have proven to be expensive, noisy, and burdensome. The objective of this work was to develop a new type of wearable monitor, an ultrasonic personal aerosol sampler (UPAS), to overcome many of the technological limitations in personal exposure assessment. The UPAS is a time‐integrated monitor that features a novel micropump that is virtually silent during operation. A suite of onboard environmental sensors integrated with this pump measure and record mass airflow (0.5–3.0 L/min, accurate within 5%), temperature, pressure, relative humidity, light intensity, and acceleration. Rapid development of the UPAS was made possible through recent advances in low‐cost electronics, open‐source programming platforms, and additive manufacturing for rapid prototyping. Interchangeable cyclone inlets provided a close match to the EPA PM2.5 mass criterion (within 5%) for device flows at either 1.0 or 2.0 L/min. Battery life varied from 23 to 45 hours depending on sample flow rate and selected filter media. Laboratory tests of the UPAS prototype demonstrate excellent agreement with equivalent federal reference method samplers for gravimetric analysis of PM2.5 across a broad range of concentrations.